The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1093/ejcts/ezab160
|View full text |Cite
|
Sign up to set email alerts
|

Results of endovascular aortic arch repair using the Relay Branch system

Abstract: OBJECTIVES Our goal was to evaluate results of endovascular aortic arch repair using the Relay Branch system. METHODS Forty-three patients with thoracic aortic pathology involving the aortic arch have been treated with the Relay Branch system (Terumo Aortic, Sunrise, FL, USA) in 10 centres. We assessed in-hospital mortality, neurological injury, treatment success according to current reporting standards and the need for secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 20 publications
1
39
0
1
Order By: Relevance
“…These are complications that adversely impact a patient's quality of life, albeit at a lower rate than that of open surgical repair ( 17 ). Indeed, our data suggest that RELAY™ Branched is associated with a more favorable neurological risk profile than that reported by colleagues, whilst also ensuring that clinicians treat these complexities with on-label device use at all times ( 8 , 15 , 18 ).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…These are complications that adversely impact a patient's quality of life, albeit at a lower rate than that of open surgical repair ( 17 ). Indeed, our data suggest that RELAY™ Branched is associated with a more favorable neurological risk profile than that reported by colleagues, whilst also ensuring that clinicians treat these complexities with on-label device use at all times ( 8 , 15 , 18 ).…”
Section: Discussionsupporting
confidence: 52%
“…Tazaki et al, in their analysis of outcomes associated with the Inoue TM triple-branched endoprosthesis, report a combined stroke rate of 40%, while Sato et al reported a 16.7% (n = 6) stroke rate with the Najuta TM fenestrated endograft (16, 18). Czerny et al observed a combined stroke rate of 20% in their series (8). Additionally, Sato et al reported that aneurysmal shrinkage post-intervention was observed in only 11 (30.6%) patients, while no change in aneurysmal size was observed in 15 (41.7%) (16).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Out of the 48 studies selected: 10 [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ] described outcomes in chimney procedures, 13 [ 1 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ] with the use of fenestrated devices, 9 [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] focused on in situ fenestration outcomes, 14 [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] on branched devices, one study compared fenestrated and branched devices [ 48 ], and one compared in situ fenestration and the chimney technique [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Clough et al [ 35 ], Ferrer et al [ 38 , 39 ], and Dai et al [ 37 ] did not report any type I endoleaks. Type IA endoleaks were described by Chen et al [ 34 ] (1 in 122 patients), Czerny et al [ 36 ] (1 in 43 patients), Kawajiri et al [ 40 ] (2 in 11), Patel et al [ 42 ] (4 in 22 patients), Tazaki et al [ 43 ] (8 in 217 patients), Verscheure et al [ 46 ] (2 in 70 patients), and Tsilimparis et al [ 44 , 45 ] (with two experiences in which 2 out of 54 patients and 1 out of 20 patients), with an incidence ranging from 0.7 to 20%. A type 1B endoleak was described by Czerny et al [ 47 ] (1 in 43 patients), Li et al [ 41 ] (1 in 16), and Tazaky et al [ 43 ] (1 in 217).…”
Section: Resultsmentioning
confidence: 99%